The relationship between education and health among incarcerated men and women in the United States. (December 2016) - Nowotny, Kathryn; Masters, Ryan; Boardman, Jason
Abstract Background This paper contributes to research on the education-health association by extending the scope of inquiry to adult inmates. Not only are inmates excluded from most nationally representative studies of health but they also represent a highly select group in terms of both education and health. As such, our study provides new information about the health of incarcerated populations and it extends the generalizability of the education-health association beyond the non-institutionalized population. Methods We use a prison-level fixed-effects regression model with the 2004 Survey of Inmates in State Correctional Facilities (n = 287 facilities) to evaluate the effects of education on a standardized morbidity scale of 11 lifetime and current health conditions among incarcerated men (n = 10, 493) and women (n = 2, 797). Results Education prior to incarceration is negatively associated with lifetime health problems for both women and men and the association is stronger among women. Among inmates who enter prison with less than a GED level of education, attaining a GED in prison is associated with better current health outcomes for men, but not women. Conclusions The generalization of the education-health association among prisoners further highlights the fundamental nature of education as a health promotive resource. Discussed are the implications for the education-health literature in general and health promotion efforts among incarcerated adults specifically.